Emerging treason?: Politics and identity in the Emerging Church Movement - Reed, Randall (Critical research on religion, 2014)
The Emerging Church is one of the more interesting new movements in the religious landscape of the United States today. The Emerging Church has come out of US Evangelicalism, which has found itself in crisis, with a diminishing number of young people remaining in the church and a general popular impression of being intolerant, judgmental, and right-wing. Many in the Emerging Church are attempting to construct a vision of Christianity that addresses these problems. However, the Emerging Church is not a monolith; it includes a variety of perspectives and positions. What I will argue in this article is that there is, among several different perspectives within the movement, a critique of the US political and economic system that provides an interesting and new way of thinking about the relationship between Christianity, politics, economics, and identity that may serve to create a challenge to the hegemonic system of the United States. For the purposes of this article I use three examples to illustrate my point: Shane Claibourne’s “New Monasticism”/”Red Letter Christians” movement; Brian McLaren’s recent work, Why did Jesus, Moses, the Buddha and Mohammed Cross The Road; and Peter Rollins as a self-proclaimed inheritor of the radical tradition. I will show that the Emerging Church thinkers, by challenging the theological constructions of US Evangelicalism, are likewise providing fodder, to varying degrees, for a critique of the US political and economic system. Whether this will coalesce into a real significant challenge or will ultimately be reabsorbed by the status quo and/or marginalized remains to be seen.